Number of Bacterial Colonies After Washing Hands with Antiseptic Soap and Regular Soap: A Study on Department of Health Analyst Students in Poltekkes Kemenkes Pontianak - Ari Nuswantoro; Maulidiyah Salim; Slamet; Dinasti Aprillia (Jurnal teknologi Kesehatan Borneo, 2020)
Hand washing is a healthy activity carried out by many parties. Getting used to wash your hands properly will increase health. The soap on the market is plain hand washing soap and antiseptic handwashing soap. The second type is claimed to be more effective in reducing the amount of bacterial contamination than plain soap because it contains antimicrobial ingredients to increase product sales. This study aims to determine the differences in the number of bacterial colonies on the palms of students who wash their hands with antiseptic soap and plain soap among students of Analyst Department of Pontianak Health Polytechnic, Minister of Health. This research was quasi-experimental, with 24 respondents. Each respondent was asked to wash hands properly twice, the first with plain soap that does not contain an antiseptic (A) and the second with soap containing antiseptic (B). After examining the number of bacteria on the respondent’s thumb, the average number of bacterial colonies got in treatments A and B was 45,5 and 38,8 CFU, respectively. Mann-Whitney U statistical test results got a probability value of 0.391> 0.05, which means there is no difference in the number of bacterial colonies in the palms that washing hands with plain soap and with antiseptic soap. This study revealed the fact that the number of bacterial colonies in the group that washed hands with antiseptic soap was lower than those who washed their hands with ordinary soap.